2023
DOI: 10.1001/jamapsychiatry.2023.0800
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Mediterranean Dietary Approaches to Stop Hypertension Intervention for Neurodegenerative Delay (MIND) Diet With the Risk of Dementia

Abstract: ImportanceDementia threatens the well-being of older adults, making efforts toward prevention of great importance.ObjectiveTo evaluate the association of the Mediterranean–Dietary Approaches to Stop Hypertension (DASH) Intervention for Neurodegenerative Delay (MIND) diet with the risk of dementia in 3 prospective studies and a meta-analysis.Design, Setting, and ParticipantsCohort analyses included the Whitehall II study (WII), the Health and Retirement Study (HRS), and the Framingham Heart Study Offspring coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…The MIND diet has been linked to slower cognitive decline 16 and lower risks of all‐cause dementia 17 and Parkinson's disease, 18 but only several cross‐sectional studies have assessed its associations with brain structural markers. In 1302 participants of the Women's Health Initiative Memory Study, adherence to a MIND‐like diet was associated with higher total and temporal lobe white matter volumes 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MIND diet has been linked to slower cognitive decline 16 and lower risks of all‐cause dementia 17 and Parkinson's disease, 18 but only several cross‐sectional studies have assessed its associations with brain structural markers. In 1302 participants of the Women's Health Initiative Memory Study, adherence to a MIND‐like diet was associated with higher total and temporal lobe white matter volumes 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown beneficial associations of the MIND diet with cognitive function and its decline, 16 all-cause dementia, 17 and Parkinson's disease, 18 which often feature structural brain changes at early stages. 19 However, associations of the MIND diet with brain structural markers remain unclear and inconsistent, and elucidating these relationships is crucial for understanding the mechanisms linking this dietary pattern to brain aging.…”
Section: Introductionmentioning
confidence: 99%
“…136 A recent meta-analysis of cohort studies showed that adherence to the MIND diet (ie, Mediterranean and dietary approaches to stop hypertension diets) in middle-aged and older adults was associated with a lower risk of incident dementia (hazard ratio, 0.83). 72 However, a recent RCT showed that the MIND diet failed to show changes in cognitive and brain MRI (WMH, hippocampal volumes, and total gray-and white-matter volumes) outcomes over 3 years among at-risk cognitively unimpaired older adults (ie, family history of AD, overweight, suboptimal diets). 137 The short duration of this trial and caloric restriction in the control group might explain the lack of difference between the randomized arms in this study.…”
Section: Other Lifestyle-related Vascular Risk Factors and Behavioral...mentioning
confidence: 99%
“…Observational studies support the protective effect of a Mediterranean diet, the DASH (Dietary Approaches to Stop Hypertension) diet, and a hybrid of the 2 called the MIND diet . However, a recent clinical trial comparing 3 years of a MIND diet with a control diet with mild caloric restriction did not demonstrate differences in global cognition or magnetic resonance imaging (MRI) findings of dementia .…”
Section: Preventionmentioning
confidence: 99%